EVALUASI PEMBELAJARAN MODEL CIPP PADA PROGRAM TAHFIDZ AL-QUR’AN DI PONDOK PESANTREN HAQ AN NAHDLIYAH SIDOARJO - An Nahdliyah, Khumairoh (ILJ: Islamic Learning Journal, 2023)
This study aims to determine the implementation process Al-Qur'an tahfidz program at the HAQ An-Nahdliyah Sidoarjo Islamic boarding school, This research uses a qualitative approach. Data collection techniques using observation, documentation, and interviews. Data analysis techniques were carried out through three stages of activity, namely data reduction, data presentation, and drawing conclusions. The results showed that the components: 1) Context, namely Islamic boarding schools have understood the Al-Qur'an tahfidz program. The legality of the program has been adjusted by the Minister of Religion regulations regarding the implementation of the Islamic boarding school program. Environmental support is very supportive in implementing the Al-Qur'an tahfidz program. The aim of the Al-Qur'an tahfidz program is to accustom children from an early age to their love for Allah and the Qur'an. 2) Input, namely HR including caregivers, teachers, administrators, and students support the implementation of the Al-Qur'an tahfidz program. Sarpras has supported the tahfidz Al-Qur'an program. The budget is sourced from the syahriah students and infaq or donors from Muslim businessmen and philanthropists. 3) Process, namely the implementation of the Al-Qur'an tahfidz program using several methods, namely audio/talaqqi, bin-nadhor, tahfidz, and kitabah, and to prevent loss of memorization, the Islamic boarding school holds a follow-up program, namely the takrir or muraja'ah program. Monitoring of the Al-Qur'an tahfidz program is carried out with teaching journals and student achievement books. Obstacles experienced in the form of frequent loss of memorization and lack of time for memorization and muraja'ah. 4) Product, namely the results of the tasmi' test scores of the students showed good results. The average I'dadiyah class test score is 80.78. And for the women's Wustho class, the average value is 77.29. For the men's Wustho class, the average score is 78.3. And for the Ulya class, the average value is 81.84